A randomised double-blind trial of cognitive training for the prevention of psychopathology in at-risk youth. (September 2020) - Mewton, Louise; Hodge, Antoinette; Gates, Nicola; Visontay, Rachel; Lees, Briana; Teesson, Maree
Abstract: Background: The aim of this study was to evaluate the effectiveness of online cognitive training as a means of reducing psychopathology in at-risk youth. Methods: In a double-blind randomised controlled trial, 228 youths (mean age = 18.6, 74.6% female) were randomly allocated to either an intervention group (n = 114; online cognitive training focused on executive functioning) and a control group (n = 114; online cognitive training focused on other cognitive abilities). Participants were assessed online at baseline, post-training, 3-, 6- and 12-month follow-up. The primary outcome of the study was overall psychopathology as measured by the Strengths and Difficulties Questionnaire. Secondary outcomes were executive functioning ability (assessed using the n-back, trail-making and Stroop tasks), day-to-day functioning and risky drinking. Results: Mixed model intention-to-treat analyses indicated that psychopathology increased and day-to-day functioning decreased, regardless of intervention group. Those in the intervention group improved more than those in the control group in terms of the n-back task, but this was not statistically significant after adjusting for multiple comparisons. There were no statistically significant effects on risky drinking, or the trail-making and Stroop tasks. Conclusion: This study failed to provide evidence for the efficacy of cognitive training as a stand-alone intervention for psychopathology. Highlights: In an at-risk sample of youth, cognitive training was not associated with improvements in psychopathology, functioning or risky alcohol use. Training was associated with improvements in working memory that were not statistically significant after adjustment for multiple comparisons. Cognitive training was not associated with improvements on measures of inhibition and task-shifting. This study questions the effectiveness of cognitive training as a stand-alone preventative strategy for psychopathology.